Citizen Insecurity and Community Transformations: An Analysis from a Psychosocial Perspective - Espinoza, Kathy Rueda; Lucas, Lourdes Mendieta; Llongo, Luis Guamán; Vera, Mónica Zea; Espín, Jesús Rodríguez (Journal of Posthumanism, 2025)
Citizen insecurity in Ecuador has evolved beyond its criminal dimension to become a multidimensional psychosocial phenomenon that is fundamentally reshaping the foundations of community life. This study examines these community transformations through a psychosocial approach, analyzing their emotional, behavioral, and social impacts. The research employed a quantitative design based on a structured survey administered to 963 participants, using an instrument organized into two analytical dimensions: Perception and Emotions (14 items) and Distrust and Social Isolation (5 items), combining dichotomous (Yes/No) and qualitative responses. The sample, predominantly female (55.2%) and concentrated in urban areas of Guayas (37.1%) and Pichincha (13.4%), revealed alarming patterns: 76.4% reported stress when traveling, 73.5% anxiety in their immediate surroundings, and 85.7% a sustained increase in worry, with fear (45%) and anxiety (34%) as the predominant emotional responses. Behaviorally, 87.4% modified daily habits, evidenced by avoidance of high-risk areas (77.6%) and restricted nighttime transportation use (80.8%). Socially, the findings demonstrated erosion of social capital, including neighbor distrust (52.4%), reduced community participation (69.9%), and relational withdrawal (78.4%). These results suggest that insecurity functions as a mechanism of social disintegration, where individual protective strategies exacerbate collective fragmentation. The study concludes that public policies must prioritize rebuilding social fabric, revitalizing public spaces as spheres of cohesion, and strengthening institutional trust, moving beyond purely punitive paradigms.